Effectiveness of Marketing 4.0 in the World of Online Advertising - Alyssa Melita Rahmat (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2021)
The development of technology has significantly changed the way society lives. In this digitalized world, every activity has been done with the help of technology, including marketing activity. Marketing has evolved in 4 eras; each era has its own distinctive and focus. Throughout this marketing revolution, online advertising has effectively been one of the best tools that significantly affect the relationship between consumers and the company. Very few studies have analyzed the effectiveness of Marketing 4.0 that combines online and offline strategy in the advertisement world and developing countries like Indonesia. Therefore, using the method of meta-synthesis aggregative as a systematic review, this study aims to dig deeper into the effectiveness of Marketing 4.0 in advertising, especially online advertising in developing countries, such as Indonesia, and how it may affect the future society or Society 5.0. This study believed that using online advertising in Marketing 4.0 is an effective way to communicate with the consumers; however, some variables should be analyzed in knowing the effectiveness of online advertising. In the future, more studies should also be done in the developing countries context so that marketers can better know how to make an advertisement.